Upaya Dosen Bimbingan Konseling Meningkatkan Kemampuan Kognitif Mahasiswa - Putri, Ananda Maha; Velina, Try (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2023)
Students' cognitive abilities are a benchmark for improving their academic achievement. High cognitive abilities will influence the student's learning achievement and achieve cum laude grades. If students' cognitive abilities increase, students will easily be active and creative in class and outside of class. Therefore, various methods are used to improve students' cognitive abilities. One of them is by providing counseling services to students through information services. In information services, a number of cognitive activities are carried out so that apart from increasing knowledge and insight, students also develop cognitive abilities. Based on these assumptions, the author conducted research with a focus on observing improving students' cognitive abilities through information services. The author conducted this research involving 45 students. Based on the results of data analysis, it is clear that cognitive abilities have increased significantly before being provided with information services and after being provided with information services. In this way, lecturers can provide information services to improve students' cognitive abilities both in class and outside of class.